TRANSFORMASI POLA PENGASUHAN ANAK PADA KELUARGA ETNIS MAKASSAR DI PERKOTAAN (Studi Kasus Pada Keluarga Etnis Makassar Di Kota Makassar Provinsi Sulawesi Selatan) - Nirwan Nirwan (SOSIORELIGIUS, 2021)
The essence of this study aims to identify and analyze parenting patterns in Makassar culture in Makassar City about the views of Makassar ethnic parents in parenting children in urban areas. The method used in this research is qualitative with a case study approach. The data collection techniques in this study were (1) non-participant observation, then the aspects observed in this study included places, actors, and activities, (2) in-depth interviews. The results show that parenting patterns for children in Makassar ethnic families, especially in Makassar City, have now undergone changes or shifts and even adaptation of values to new values in both form and nature. Some of the factors that cause this to happen are (1) factors of change and shifting times with the previous generation, (2) individual psychological factors of children, and (3) factors of binding legislation relating to children.